2020
DOI: 10.3390/app10020720
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance Forecasting of Residential Buildings Using Fuzzy Approaches

Abstract: The energy consumption used for domestic purposes in Europe is, to a considerable extent, due to heating and cooling. This energy is produced mostly by burning fossil fuels, which has a high negative environmental impact. The characteristics of a building are an important factor to determine the necessities of heating and cooling loads. Therefore, the study of the relevant characteristics of the buildings, regarding the heating and cooling needed to maintain comfortable indoor air conditions, could be very use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Literature analysis has shown that statistical and artificial neural network-based models are most commonly used, while fuzzy logic-based models are used much less frequently. A fuzzy approach for determining the energy performance of buildings was applied by Nebot and Mugica [34], where two methods were used for prediction: fuzzy inductive inference (FIR) and adaptive neuro-fuzzy inference system (ANFIS). The study was performed on a set of simulated residential buildings developed by Tsanas and Xifara [30].…”
Section: Literature Review Of Estimation Methods For Building's Energ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature analysis has shown that statistical and artificial neural network-based models are most commonly used, while fuzzy logic-based models are used much less frequently. A fuzzy approach for determining the energy performance of buildings was applied by Nebot and Mugica [34], where two methods were used for prediction: fuzzy inductive inference (FIR) and adaptive neuro-fuzzy inference system (ANFIS). The study was performed on a set of simulated residential buildings developed by Tsanas and Xifara [30].…”
Section: Literature Review Of Estimation Methods For Building's Energ...mentioning
confidence: 99%
“…The study was performed on a set of simulated residential buildings developed by Tsanas and Xifara [30]. The computational results obtained by the authors [34] have been compared with the results obtained for the same input data (for simulated buildings) using static and artificial neural networkbased methods [25,28,30,31]. The results showed that the use of methods based on fuzzy logic gives very good results in predicting energy consumption [34].…”
Section: Literature Review Of Estimation Methods For Building's Energ...mentioning
confidence: 99%
“…Using a hybrid method frequently requires long computation time because of the boundary advancement procedure and master information during the model improvement process [84]. There have been studies on hybrid methods that have focused on electrical consumption [85][86][87][88][89][90][91][92], cooling and heating load [79,80,[93][94][95], energy consumption [96][97][98][99][100][101], thermal load [102], thermal response [103] and load demand [104]. Based on the aforementioned studies, a summary of their contributions and limitations is presented in Table 3.…”
Section: ] Yumentioning
confidence: 99%
“…Bose et al [17] reviewed the contribution in the area of Fuzzy time series (FTS) forecasting, these models have proven to be a powerful tool for modelling and forecasting complex systems in different domains including energy, economics, biology, etc. One of this technique is the Fuzzy Inductive Reasoning (FIR), which has used for energy forecasting in residential buildings and smart grid [18,19].…”
Section: Related Workmentioning
confidence: 99%